Identification of the chemical constituents of Curcuma caesia (Black Turmeric) Hydrosol extracted by hydro-distillation method - Lee, Choon Fatt; Nurul Waheeda, Abdu Rahman; Mohd Aizudin, Abd Aziz; K, M Isa (IOP Publishing, 2021)
Curcuma caesia (black turmeric), a perennial herb that has a distinguishable bluish-black rhizome with a bitter and pungent smell and is widely used and extracted for its medicinal values. C. caesia extracted by hydro-distillation method produce essential oil and hydrosol. The essential oil of C. caesia is known for its high medicinal value, but the chemical constituent of the hydrosol is yet to be studied. Hence, this study will investigate the chemical constituent of the hydrosol of C. caesia’s rhizome extracted by hydro-distillation to comprehend the benefits and usages of the hydrosol produced for further research in pharmaceutical and natural products industries. Besides, hydro-distillation is carried out in different temperatures to study the effect of temperature on the active compounds in the hydrosol. Hydro-distillation of powdered rhizome is use to obtain the hydrosol of C. caesia at the temperature of 60°C, 80°C and 100°C before being separated by using a rotary evaporator. The sample is then analyze by using Gas chromatography–mass spectrometry (GC-MS) and Fourier transform infrared (FTIR). From FTIR analysis, the functional groups found in the hydrosol were OH, C=C and -NH groups. As the temperature increased, more components were decomposed. Hence, lesser functional groups were found in the hydrosol at 100°C as compared to 60°C. Chemical constituents of the hydrosol of C. caesia were identified by GC-MS analysis, with camphor (0.57%) as the only major component at 100°C. Comparing the chemical constituents of the hydrosol at 60°C and 80°C, the elevated temperature of hydro-distillation caused decomposition of the chemical constituents of the hydrosol due to changes of properties. The chemical constituents of the hydrosol of C. caesia were significantly different from the essential oil qualitatively and quantitatively, with the medicinal value of the hydrosol was uncertain due to the trace amount of camphor and other chemical constituents possessed in the hydrosol.